2013
DOI: 10.1152/ajpcell.00404.2012
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of smooth muscle-specific ion channels in TGF-β1-treated human adipose-derived mesenchymal stem cells

Abstract: Lee SY, Kim JH, Han J. Functional expression of smooth muscle-specific ion channels in TGF-␤1-treated human adipose-derived mesenchymal stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 70 publications
1
38
0
Order By: Relevance
“…In BM-derived adult human MSCs, SMAD family member 3 (SMAD3)-dependent nuclear translocation of β-catenin is required for TGF-β1-induced proliferation (24). Previous studies suggested that TGF-β1 induces increased expression levels of vascular smooth muscle cell (SMC)-like ion channels and the differentiation of human adipose tissue-derived MSCs into contractile vascular SMCs (25).…”
Section: Introductionmentioning
confidence: 99%
“…In BM-derived adult human MSCs, SMAD family member 3 (SMAD3)-dependent nuclear translocation of β-catenin is required for TGF-β1-induced proliferation (24). Previous studies suggested that TGF-β1 induces increased expression levels of vascular smooth muscle cell (SMC)-like ion channels and the differentiation of human adipose tissue-derived MSCs into contractile vascular SMCs (25).…”
Section: Introductionmentioning
confidence: 99%
“…20 BK Ca channels play a negative feedback inhibition of muscular tone in VSMCs (vascular smooth muscle cells) 21 and maintain myogenic tone in SMCs of the superior epigastric arteries. 22 Furthermore, a similar negative feedback regulatory mechanism of BK Ca channels was found in cerebral arteries. 15 Our findings showed that hypercholesterolemia increased contraction of the SO and downregulated Tyr-phosphorylation of BK Ca a-subunits suggested that BK Ca channels may also contribute to negative feedback inhibition on the contraction of SOSMCs in HC rabbits, and the tyrosine phosphorylation of BK Ca a-subunit may be a critical factor in functional regulation of SO muscle relaxation.…”
Section: Discussionmentioning
confidence: 65%
“…These differentiated human endothelial cells were confirmed by RT-PCR for the expression of the human endothelial cell markers CD31, CD34, CD144, and eNOS; moreover, the differentiated cells were incorporated into new vessels (3). Treatment of adipose-derived human MSCs with transforming growth factor-1 (TGF-1) was shown to induce formation of vascular smooth muscle cells in vitro and to enhance blood flow, capillary density, and vessel formation in vivo; moreover, decreased tissue necrosis was observed in vivo (10). When genetically modified placenta-derived human MSCs transformed with adenoviral bicistronic vectors expressing FGF2 and PDGF–BB were transplanted into an ischemic hindlimb mouse model, collateral vessel formation, capillary density, and arteriole density all markedly increased (11).…”
Section: Modified Methods For Enhancing Angiogenesismentioning
confidence: 99%